Translation studies considerations on the interrelationship between health-medical language and the literary language - Huertas, Cristina (Íkala, Revista de Lenguaje y Cultura, 2010)
This paper aims to study the existing interrelation between two specialized languages that are apparently opposed: the literary and medical languages. Besides, the study comprised three different stages: 1) analysis and description of both literary and medical languages individually; 2) creation of a corpus consisting of real, representative texts from the literary and medical fields; and 3) comparative analysis of the interrelations between these two languages. The interrelation between these two specialized languages is clear, specifically for the English and Spanish languages, since different words and terms are shared in order to include new nuances. Furthermore, the translation of both types of texts studied in this paper requires an efficient use of data and documentation sources, which together with translation strategies, are unavoidable to solve the problems derived from cultural aspects such as anisomorphisms. Even though specialized languages have been studied separately, the interrelation between them, and the extrapolation of terms and concepts of one specialized language to another, can be clearly observed. Moreover, the translator should know the asymmetrical relation between two texts, or even two languages, due to the anisomorphisms, especially cultural anisomorphisms, to avoid inaccuracies in their translations.